The Alternative Complement System Mediates Cell Death in Retinal Ischemia Reperfusion Injury - Inafuku, Saori; Klokman, Garrett; Connor, Kip M. (Frontiers in Molecular Neuroscience, 2018)
Ischemia reperfusion (IR) injury induces retinal cell death and contributes to visual impairment. Previous studies suggest that the complement cascade plays a key role in IR injury in several systemic diseases. However, the role of the complement pathway in the ischemic retina has not been investigated. The aim of this study is to determine if the alternative complement cascade plays a role in retinal IR injury, and identify which components of the pathway mediate retinal degeneration in response to IR injury. To accomplish this, we utilized the mouse model of retinal IR injury, wherein the intraocular pressure (IOP) is elevated for 45 min, collapsing the retinal blood vessels and inducing retinal ischemia, followed by IOP normalization and subsequent reperfusion. We found that mRNA expression of complement inhibitors complement receptor 1-related gene/protein-y (Crry), Cd55 and Cd59a was down-regulated after IR. Moreover, genetic deletion of complement component 3 (C3−/−) and complement factor b (Fb−/−) decreased IR-induced retinal apoptosis. Because vascular dysfunction is central to IR injury, we also assessed the role of complement in a model of shear stress. In human retinal endothelial cells (HRECs), shear stress up-regulated complement inhibitors Cd46, Cd55, and Cd59, and suppressed complement-mediated cell death, indicating that a lack of vascular flow, commonly observed in IR injury, allows for complement mediated attack of the retinal vasculature. These results suggested that in retinal IR injury, the alternative complement system is activated by suppression of complement inhibitors, leading to vascular dysfunction and neuronal cell death.